DEVELOPMENT OF ANDROID-BASED PETA (PENJELAJAHAN MATEMATIKA) LEARNING MEDIA ON SPEED LEARNING MATERIALS AT A FIFTH-GRADE ELEMENTARY SCHOOL - Salsabila Baliani Putri Sopian; I. Isrokatun; Ali Ismail (Laboratorium Program Studi Pendidikan Guru Sekolah Dasar, 2023)
This paper describes the developmental process of PETA (Penjelajahan Matematika) learning media based on the Android application on speed learning materials at a fifth-grade elementary school, determines the feasibility of the application through the validation process of experts, and finds out the compatibility of applications in several devices with different Android versions. The research uses a research and Development (RnD) method with the ADDIE model (Analysis, Design, Development, Implementation, Evaluation). The results of the research are (1) the development of the PETA application is relevant to the needs of the mathematics learning process on speed learning material at class V SD, (2) the design of the PETA application is adopted from the concept of exploring games with various forms of presentation, (3) the PETA application design that has been made is developed into file.apk., (4) the PETA application has the feasibility of the content in the very feasible category with a percentage of 97%, the feasibility of the media in the very feasible category with a percentage of 92.75%, and already fulfilled the standard of portability on adaptability and installability aspects with a testing percentage of 100%, and (5) the final product of the PETA application is developed based on the evaluation results at the testing stage of functional suitability and portability by making minor improvements to the instruction aspects of the use and the additional menu of an